Progress Towards the Knowledge-Based Economy - Norbert Knoll (Austrian Institute of Economic Research (WIFO), 2001)
During the last decade, policy-makers have increasingly devoted attention to the factors that influence the rate and direction of innovation. In particular, developments in the ICT sector have been discussed as a currently dominant source of both technological change and overall economic growth. The visible limitations of this approach and an improved understanding of the innovation process have widened the perspective. Essentially, industrial innovation is a process of knowledge creation and the outcome depends on the learning that takes place at the level of individuals, firms, sectors and nations. Consequently, analytical concepts which focus on capabilities and competencies, as well as other factors which constitute a specific learning environment, have attracted attention. In this paper1, we start by discussing the essential assumptions and implications of concepts such as the Knowledge-Based Economy; by comparing current ideas with earlier approaches which focused on the role of information and ICTs, some distinct features will be drawn to attention. The subsequent section is devoted to the two main dimensions of knowledge generation: skill base and interactivity. Both aspects are conducive to the examination of empirical evidence at the country level. Finally, policy options from the perspective of knowledge will be discussed. As several examples of the policies which support innovation reveal, Member States have developed new strategies which address the challenge of improving the framework for knowledge generation in the economy.
Keywords: 330; Information Society; Wissensgesellschaft; Informationstechnik; Technischer Fortschritt; Humankapital